Modèle de prévision et de simulation de l’aide sociale au Québec - Gautrin, J.-F.; Verdon, B. (L'Actualité économique)

(untitled) (HEC Montréal, 1974)
AbstractThis paper deals with a macro-simulation and forecasting model, called PASSIM, essentially markovian, of the working of the Quebec system of Public Assistance. It has to do with both the numbers of persons involved and with the expenditures. It became fully operational in the summer of 1972 albeit it still contains a number of important imperfections.The model relies on a linear programming procedure to estimate probability transition matrices. This seems to represent one of the original features of the model. The basic philosophy of the Quebec Public Assistance is simple: a modified version of a guaranteed income program. This needs test is simply used to constitute the submodel for the determination of allowances. Transition matrices are three dimensional; transition probabilities may change over time due to changes in various exogeneous variables.The model is particularly oriented to test some major changes in the law. An example of a typical simulation is presented and some gross sensitivity tests are also given.